Very short-term earthquake precursors from GPS signal interference based on the 2013 Nantou and Rueisuei earthquakes, Taiwan. (15th December 2015) - Yeh, Yu-Lien; Cheng, Kai-Chien; Wang, Wei-Hau; Yu, Shui-Beih
Highlights: Prominent anomalous GPS signals were observed a few minutes before the occurrence of earthquakes. GPS phase has been greatly disturbed before the earthquakes. The source of disturbance emits from the seismogenic region. The anomalous GPS signal is caused by the interference between the GPS phase and EM. The anomalous GPS signals observed in this study can act as earthquake precursor. Abstract: We set up a GPS network with 17 Continuous GPS (CGPS) stations in southwestern Taiwan to monitor real-time crustal deformation. We found that systematic perturbations in GPS signals occurred just a few minutes prior to the 2013 Nantou ( M L = 6.5) and Rueisuei ( M L = 6.4) earthquakes in Taiwan. The anomalous pseudorange readings were several millimeters higher or lower than those in the background time period. These systematic anomalies were found as a result of interference of GPS L-band signals by electromagnetic emissions (EMs) prior to the mainshocks. The EMs may occur in the form of harmonic or ultra-wide-band radiation and can be generated during the formation of Mode I cracks at the final stage of earthquake nucleation. We estimated the directivity of the likely EM sources by calculating the inner product of the position vector from a GPS station to a given satellite and the vector of anomalous ground motions recorded by the GPS. The results showed that the predominant inner product generally occurred when the satellite was in the direction either toward or away from the epicenter with respect to the GPS network. Our findings suggest that the GPS network may serve as a powerful tool to detect very short-term earthquake precursors and presumably to locate a large earthquake before it occurs. Nevertheless, a direct measurement of EMs at the site of the GPS array is required in future studies to confirm this hypothesis.